Enhancing Patient Safety Through Interprofessional Education And Practice Integration: A Study Of General Practitioners, Operating Room Technicians, Nurses, Radiologists, And Health Administrators In Primary Care Settings (The Review of Diabetic Studies, 2024)
The communication gaps and compartmentalized professional roles among the general practitioners, operating room staff, nurses, radiology staff, and health administrators in the primary care setting still exist putting the patient safety at risk. This study investigates the ways in which interprofessional education (IPE) and practice integration can improve safety by means of collaborative training, shared competences, and interventions that are carried out by teams.In the study, significant goals such as fewer diagnostic mistakes, improved medication reconciliation, and lower adverse event rates are identified. These outcomes are derived from a synthesis of previous literature, which includes simulation-based programs and frameworks such as TeamSTEPPS and IPEC skills. It is important to stress the contributions that are distinctive to each role, such as the fact that general practitioners are in charge of diagnostic monitoring, nurses and radiologists guarantee that imaging is accurate, operating room personnel strengthen procedural hygiene, and administrators build safety cultures.The challenges like time constraints and hierarchical barriers can be solved with the usage of scaled primary care adaptations. The results suggest the inclusion of necessary IPE curriculum in primary care education, policy encouragement of co-located teams and longitudinal follow-ups to sustain changes, which will eventually result in the endorsement of a patient-centered safety ecosystem.